Program mentoring Pendidikan Agama Islam di Perguruan Tinggi Umum - Gani, Ridwan Abdul; Indra, Hasbi (Tawazun: Jurnal Pendidikan Islam, 2025)
Learning Islamic Religious Education (PAI) in public universities still faces various challenges, such as learning strategies, quality of lecturers, as well as curriculum and number of credits. This research aims to: (1) analyze Hasan Al-Banna’s Usrah program in the book Wasailut Tarbiyah Inda Ikhwanil Muslimin by Ali Abdul Halim Mahmud, (2) analyze the PAI Assistance program at Bogor Agricultural University (IPB University), and (3) formulate a PAI Mentoring program design that can be applied in public universities. This research used a qualitative approach with literature study and field research methods. The literature study was conducted through book content analysis to understand the structure and components of the usrah program, while the field study was conducted by observing the practice of PAI Mentoring program at IPB. The results showed that there are fundamental similarities between the two programs, which consist of 12 main components including objectives, participants, educators, management, time, place, methods, curriculum, regulations, evaluation, facilities, as well as financial management and problems. These similarities are then synthesized into a PAI Mentoring program model that can be a reference for implementation at PTU. The conclusion of this study confirms the importance of preparing a clear, relevant, sustainable, innovative, and collaborative mentoring program to be effective in fostering students. Abstrak Pembelajaran Pendidikan Agama Islam (PAI) di perguruan tinggi umum masih menghadapi berbagai tantangan, seperti strategi pembelajaran, kualitas dosen, serta kurikulum dan jumlah SKS. Penelitian ini bertujuan untuk: (1) menganalisis program Usrah Hasan Al-Banna dalam kitab Wasailut Tarbiyah Inda Ikhwanil Muslimin karya Ali Abdul Halim Mahmud, (2) menganalisis program Asistensi PAI di Institut Pertanian Bogor (IPB University), dan (3) merumuskan desain program Mentoring PAI yang dapat diterapkan di perguruan tinggi umum. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka dan penelitian lapangan. Studi pustaka dilakukan melalui analisis isi kitab untuk memahami struktur dan komponen program usrah, sedangkan studi lapangan dilakukan dengan mengamati praktik program Asistensi PAI di IPB. Hasil penelitian menunjukkan terdapat kesamaan mendasar antara kedua program, yaitu terdiri dari 12 komponen utama yang meliputi tujuan, peserta, pendidik, manajemen, waktu, tempat, metode, kurikulum, peraturan, evaluasi, sarana, serta pengelolaan keuangan dan masalah. Kesamaan ini kemudian disintesis menjadi model program Mentoring PAI yang dapat menjadi acuan pelaksanaan di PTU. Simpulan dari penelitian ini menegaskan pentingnya penyusunan program mentoring yang jelas, relevan, berkelanjutan, inovatif, dan kolaboratif agar efektif dalam membina mahasiswa.